2016
DOI: 10.1038/tp.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

MAOA gene hypomethylation in panic disorder—reversibility of an epigenetic risk pattern by psychotherapy

Abstract: Epigenetic signatures such as methylation of the monoamine oxidase A (MAOA) gene have been found to be altered in panic disorder (PD). Hypothesizing temporal plasticity of epigenetic processes as a mechanism of successful fear extinction, the present psychotherapy-epigenetic study for we believe the first time investigated MAOA methylation changes during the course of exposure-based cognitive behavioral therapy (CBT) in PD. MAOA methylation was compared between N=28 female Caucasian PD patients (discovery samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 39 publications
8
113
0
7
Order By: Relevance
“…Thus, despite comparability to previous treatment-epigenetic studies regarding size (e.g., Ziegler et al, 2016), replication in larger samples as well as in mixed samples including also male patients is warranted. Given that no control group was available paralleling the time course of treatment in the patient sample, the observed changes in MAOA methylation in patients cannot conclusively be attributed to the effects of the intervention but could rather be an inconsequential side effect arising from a significant environmental stimulus.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, despite comparability to previous treatment-epigenetic studies regarding size (e.g., Ziegler et al, 2016), replication in larger samples as well as in mixed samples including also male patients is warranted. Given that no control group was available paralleling the time course of treatment in the patient sample, the observed changes in MAOA methylation in patients cannot conclusively be attributed to the effects of the intervention but could rather be an inconsequential side effect arising from a significant environmental stimulus.…”
Section: Discussionmentioning
confidence: 91%
“…In anxiety disorders, besides the above-mentioned study (Ziegler et al, 2016) only 2 other studies have investigated methylation dynamics with respect to treatment effects. Here, methylation changes in the serotonin transporter ( 5-HTT ) gene as well as in the FK506-binding protein 5 ( FKBP5 ) gene were found to be associated with response to psychotherapy in children with mixed primary anxiety disorder diagnoses and obsessive-compulsive disorder (Roberts et al, 2014, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Robust evidence shows that MAOA genotype moderates the association between maltreatment and mental disorders (Wermter et al 2010; Mandelli and Serretti 2013; Byrd and Manuck 2014), and recent evidence shows associations between MAOA methylation and mental disorders (Melas et al 2013; Melas and Forsell 2015; Checknita et al 2015; Ziegler et al 2016). Furthermore, our study, and others (Melas et al 2013; Melas and Forsell 2015; Ziegler et al 2016), showed that genotype and environmental trauma independently associate with MAOA ROI methylation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among women with panic disorder who responded positively to cognitive-behavioural therapy, methylation levels rose to equal those observed among healthy women, while no significant change in methylation was detected among treatment non-responders (Ziegler et al 2016). Although the role of MAOA-uVNTR genotype in treatment response is not fully understood, recent studies suggest that men and women carrying MAOA-S, as compared to MAOA-L carriers, display greater reductions in symptoms of depression when taking mirtazapine (Tzeng et al 2009) and of panic disorder following cognitive-behavioural treatment (Reif et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, she also showed that the lack of positive life events rather than the accumulation of negative events explained monoamine oxidase hypomethylation. Recently, she and her team demonstrated that psychotherapy has the power to reverse monoamine oxidase hypomethylation, possibly leading to lasting treatment effects [34]. While these findings are preliminary, they demonstrate the potential of epigenetics to identify environmental factors beyond classical stress models and to elucidate the molecular mechanisms of behavioral change and personal growth.…”
Section: A Neuroscience Vision For Engel's Unified Concept Of Health mentioning
confidence: 99%